Increase of nitrogen-use efficiency by phosphorus fertilization in grass-legume pastures - Francisquini Junior, Amarildo; Calonego, Juliano Carlos [UNESP]; Rosolem, Ciro Antonio [UNESP]; Santos, Carlos Henrique dos; Tiritan, Carlos Sergio (Springer, 2020)
Forage legumes intercropped with grasses add nitrogen (N) to the production system and may increase forage yields. However, both phosphate fertilization and the solubility of phosphorus (P) sources may affect this contribution. This study aimed to evaluate the response of Guinea grass (Panicum maximum) intercropped with legumes and fertilized with phosphate fertilizers of different solubility. Guinea grass was grown as a single crop, fertilized or not with mineral N, and intercropped with Java (Macrotyloma axillare), or dwarf pigeon pea (Cajanus cajan); phosphorus was applied as triple superphosphate (P-TSP) or Bayovar (P-Bay), plus a control without phosphorus. The highest forage yield and N accumulation was observed in Guinea grass fertilized with N and P, with 70,364 and 60,036 kg ha(-1)of dry matter, resulting in 977 and 1004 kg ha(-1)of N accumulated by the plants for P-TSP and P-Bay, respectively. The introduction of legumes increased the N accumulation but decreased yield of Guinea grass. The highest nitrogen use efficiency (NUE) was found with P fertilization, i.e., 56% and 54% for P-TSP and P-Bay, respectively. The use of legumes intercropped with Guinea does not improve the effectiveness of the reactive rock phosphate. Therefore, the introduction of legumes intercropping with Guinea grass may be an alternative to N fertilization only when P is not applied to low fertile soils. Broadcast and incorporated P fertilization by the time of Guinea grass sowing, not only increases forage yields but also results in higher NUE regardless of P fertilizer solubility.
Keywords: Phosphate sources; Intercropped pasture; Panicum maximum; Cajanus cajan; Macrotyloma axillare